2003
DOI: 10.1007/s00417-002-0620-6
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumor cerebri associated with Sjögren's syndrome

Abstract: Sjögren's syndrome should be considered in the different etiologies of pseudotumor cerebri. The major improvement with corticosteroids and ventriculoperitoneal shunt makes prompt diagnosis essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Increased ICP has been noted as the initial manifestation of some systemic inflammatory disorders, including lupus, Sjogren’s syndrome, and Kawasaki disease 6 7 8 . We posit that our patients’ increased ICP similarly reflects systemic inflammation related to SARS-CoV-2 infection, resulting in central nervous system (CNS) effects.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ICP has been noted as the initial manifestation of some systemic inflammatory disorders, including lupus, Sjogren’s syndrome, and Kawasaki disease 6 7 8 . We posit that our patients’ increased ICP similarly reflects systemic inflammation related to SARS-CoV-2 infection, resulting in central nervous system (CNS) effects.…”
Section: Discussionmentioning
confidence: 99%
“…The facial nerve supplies the autonomic function of the salivary and the lacrimal glands. A few cases of Sicca syndrome94 were reported in patients with IICH. According to this hypothesis, this may be due to the compression of the autonomic fibers running toward the salivary and lacrimal glands.…”
Section: Symptoms Associated With Increased Icpmentioning
confidence: 99%
“…A report has suggested that central nervous system symptoms can be the initial manifestation of pSS when mild complaints of sicca symptoms are overlooked. [ 2 ] No associated conditions linked to benign intracranial hypertension syndrome were seen in our patient. The pathophysiological mechanism of intracranial hypertension in pSS remains unknown.…”
mentioning
confidence: 74%
“…venous thrombosis, medication side effects, vasculitis, immune complex precipitation or even direct antibody injury). [ 1 2 3 4 ] This case expands the spectrum of presentation of pSS that has an important impact in the long-term timely management of such patients.…”
mentioning
confidence: 92%
See 1 more Smart Citation